Effects of corn variety in whole-plant corn silage on dry matter intake, average daily gain and gastrointestinal tract bacteria and metabolites in Hu lambs - Jiao, Jianxin; Ma, Shumin; Jiao, Ting; Shi, Shangli; Gao, Yongquan; Zhang, Xia; Zhao, Shengguo; Degen, A. Allan (Frontiers in Microbiology, 2025)
IntroductionWhole-plant corn silage (WPCS) is an important roughage source in ruminant nutrition, and its nutritional value can vary significantly with corn variety. Understanding how different WPCS varieties influence gastrointestinal microbiota and metabolic profiles is essential for optimizing feed efficiency and animal health.MethodsThis study examined the effects of three corn varieties (2 introduced - Tunyu 168: TY; Yu silage 23: YQZ, and 1 local Longsheng 1: LS) in WPCS on gastrointestinal bacteria and metabolites in lambs. Thirty 4-month-old female Hu lambs (19.6 ± 0.26 kg) were assigned randomly to three groups (n = 10 per groups). After 90 days, 6 random lambs from each group were slaughtered, and contents from the rumen, ileum and cecum were collected.ResultsThe LS silage had the highest crude protein (CP) content, the TY silage had the lowest neutral detergent fiber (NDF) content, and the YQZ silage had the highest ammonia nitrogen (NH3-N) content. Dry matter intake (DMI) was greater in lambs fed the YQZ and TY silages than the LS silage, while average daily gain (ADG) was greater in lambs fed the TY silage than the YQZ and LS silages. The greatest concentration of total volatile fatty acids (TVFAs) in the rumen was measured in lambs fed the YQZ silage, and in the ileum and cecum was measured in lambs fed the TY silage. Lambs fed the YQZ silage increased the relative abundances of bacteria that degrade carbohydrates and synthesize volatile fatty acids (VFAs) in the gastrointestinal tract, and decreased the relative abundances of pathogenic bacteria in the rumen; while lambs fed the TY silage increased the relative abundances of bacteria in the cecum that degrade carbohydrate, protein and starch, and decreased the relative abundances of pathogenic bacteria in the rumen. The pathways of nicotinate and nicotinamide metabolism and folate biosynthesis were upgraded with the TY silage; whereas, pentose phosphate metabolism, histidine metabolism and folate biosynthesis were upgraded with the YQZ silage.ConclusionThese findings suggests that the YQZ and TY silages mediate rumen fermentation by altering rumen bacterial populations and metabolic activities, thereby maintaining rumen health and improving lamb growth performance. Lambs fed the TY silage had the greatest ADG and best feed conversion ratio (FCR: DMI/ADG), but the YQZ silage may have greater potential in sheep as it mediates a wider range of metabolic pathways.